1989
DOI: 10.1121/1.398306
|View full text |Cite
|
Sign up to set email alerts
|

Comments on ‘‘The negative effect of amplitude compression in multichannel hearing aids in the light of the modulation-transfer function’’ [J. Acoust. Soc. Am. 8 3, 2322–2327 (1988)]

Abstract: According to Plomp [J. Acoust. Soc. Am. 83, 2322–2327 (1988)], fast multichannel amplitude compression has a predictably negative effect on speech intelligibility for both normal and impaired listeners. The following letter is a response to that conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…A multiband syllabic compression system with more than several channels (for example 8 or 16) was first advocated by Villchur (1973). Since then, its effects on speech as well as its interactions with characteristics of impaired hearing have been controversial (Villchur, 1973(Villchur, , 1989Plomp, 1988). On the other hand, multiband compression systems with a small number of bands (two or three) can improve the ability to understand speech in a noisy environment (Laurence et al, 1983;Moore, 1987;, 1988Moore et al, 1985Moore et al, , 1991Moore et al, , 1992Ringdahl et al, 1990).…”
Section: Previous Work With Compressionmentioning
confidence: 97%
“…A multiband syllabic compression system with more than several channels (for example 8 or 16) was first advocated by Villchur (1973). Since then, its effects on speech as well as its interactions with characteristics of impaired hearing have been controversial (Villchur, 1973(Villchur, , 1989Plomp, 1988). On the other hand, multiband compression systems with a small number of bands (two or three) can improve the ability to understand speech in a noisy environment (Laurence et al, 1983;Moore, 1987;, 1988Moore et al, 1985Moore et al, , 1991Moore et al, , 1992Ringdahl et al, 1990).…”
Section: Previous Work With Compressionmentioning
confidence: 97%
“…As a result, greater masking release might be expected to occur with WDRC than with linear amplification. On the other hand, improved audibility may (Plomp, 1988) or may not (Villchur, 1989) be offset by increased temporal distortion or comodulation of speech with the masker, especially when the masker is competing speech (Stone & Moore, 2007, 2008, resulting in similar or even less masking release.…”
Section: Hearing Statusmentioning
confidence: 99%
“…To the extent that random amplitude fluctuations in the masker impede speech understanding, fast WDRC might improve masking release by minimizing these envelope fluctuations (Glasberg & Moore, 1992;Stone & Moore, 1992). Again, this benefit could come at a cost of increased distortion of speech with fast WDRC (Plomp, 1988; but see Villchur, 1989). Alexander and Masterson (2015) examined the influence of the number of compression channels and of slow and fast release times for WDRC on the perception of speech in unmodulated noise and modulated noise for adults with hearing loss.…”
Section: Compression Speedmentioning
confidence: 99%
“…Some (e.g., Plomp, 1988) have argued that compression in general may be detrimental to speech intelligibility due to its effect on the modulation spectrum as quantified by the speech transmission index (STI). Others (Noordhoek & Drullman, 1997;Villchur, 1989) have argued that the reduction in intelligibility in noise can not be attributed to the reductions in envelope modulations alone but may occur because the weaker elements of speech are masked. Villchur (1973) showed that the weak elements of speech can be preserved to some degree with two-band compression.…”
Section: Discussionmentioning
confidence: 96%